Road safety is very much a public health concern - Abd Razak, Dzulkifli (2004)
Amidst the preoccupation about violence in schools, cases of indiscipline during the National Service programme and the contentious issues regarding the measles vaccine, the World Health Day passed almost unnoticed last week. Malaysians it seemed had too much on their plates to be reminded of another devastating unresolved issue – road safety. This year’s theme for the World Health Day is “Road Safety is No Accident”. It is very appropriate for Malaysians since many of our road tragedies are indeed “no accident”. As mentioned by the United Nations SecretaryGeneral Kofi Annan, in conjunction with the occasion, road safety can prevent needless suffering.